2020
DOI: 10.1103/physrevb.101.024425
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization switching in bistable nanomagnets by picosecond pulses of surface acoustic waves

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…When strain (strain amplitude of 0.5%) is applied, the system shows a large-angle magnetization precession and switching occurs in 3 ns. We also note that Vlasov et al ( 46 ) have recently predicted switching in an elliptical nanomagnet with shape anisotropy.…”
Section: Discussionsupporting
confidence: 62%
“…When strain (strain amplitude of 0.5%) is applied, the system shows a large-angle magnetization precession and switching occurs in 3 ns. We also note that Vlasov et al ( 46 ) have recently predicted switching in an elliptical nanomagnet with shape anisotropy.…”
Section: Discussionsupporting
confidence: 62%
“…As we have demonstrated that the model works well in the absence of an phenomenological Gilbert damping, which consists mainly of electronic contributions, the SLD model can be employed to study magnetic insulators, such as YIG, where the principal contribution to damping is via magnon-phonon interactions. Future application of this model includes controlling the magnetisation via THz phonons 7 which can lead to non-dissipative switching of the magnetisation 11,12 . With the increased volume of data stored, field-free, heat-free switching of magnetic bits could represent the future of energy efficient recording media applications.…”
Section: Discussionmentioning
confidence: 99%
“…The excitation of THz phonons leads to a magnetic response with the same frequency in Gd 7 , proving the necessity of considering the dynamics of both lattice and spins. Phonon excitations can modulate both anisotropy and exchange which can successfully manipulate [8][9][10] or potentially switch the magnetisation 11,12 , ultimately leading to the development of low-dissipative memories.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the symmetry of N , equation (7), and hence all its roots, remains independent on the direction of H and the equilibrium magnetization m 0 with respect to the wave propagation direction along the z -axis. For each positive wavenumber k , the determinant ( 7) is solved for ω.…”
Section: Inertial Exchange Magnons In Samples With Spherical Symmetrymentioning
confidence: 99%
“…After the first description of the dynamics of the magnetization by Landau and Lifshitz [1], Gilbert proposed an equation that contains a correction due to the precessional damping [2,3]. Since then, the so-called Landau-Lifshitz-Gilbert (LLG) equation is known to give an excellent description of the dynamics of the magnetization, including ferromagnetic resonance (FMR) and magnetostatic waves [4,5], as well as the magnetization reversal [6,7]. Ferromagnetic resonance and time-resolved magnetization measurements allow its spatially homogeneous precession (k = 0) but also non-uniform modes of the magnetization precession (k = 0, where k is the wave vector of spin waves) to be measured [8][9][10].…”
Section: Introductionmentioning
confidence: 99%